(untitled) - Anderson, Jerry (Indianapolis, I.N., 1997)
Introduction to activex; Activex automation servers; Activex controls; Com objects and custom interfaces; Using your component and advanced topics.
Keywords: C++ (Computer program language),C++ (ngôn ngữ chương trình máy tính)